Correction: Cost-effectiveness of Left Ventricular Assist Devices (LVADs) as destination therapy in the UK: An economic modelling study. - Tuba Saygın Avşar; Louise Jackson; Pelham Barton; Sophie Beese; Hoong S Lim; David Quinn; Malcolm Price; David J Moore (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0312912.].